What and How to Assess Teacher’s Performance? A Proposal Based on the Factors that Support Learning - Carlos Guzmán, Jesús (2016)
A proposal is presented to assess teacher’s performance based on the aspects that educational research has found as fundamental to achieve students’ learning. The proposal is aimed mainly at teachers and people responsible for teacher’s assessment programs. After criticizing the traditional way of assessing teacher’s performance, it is shown a different way of doing it considering four essential dimensions of teaching: Knowledge of what is taught, management of didactic aspects, teacher’s didactic thinking and teacher motivation, responsibility and self-efficacy. It is described and justified what and how to assess, suggesting to do it by observing the educational practice. Therefore, guidelines are provided to assess it, pointing out the didactic aspects that are considered essential for students to acquire knowledge. It ends pointing out its advantages and giving some recommendations to apply it.